Interdisciplinary Review of Demonic Possession Between 1890 and 2023: A Compendium of Scientific Cases - Escolà-Gascón, Álex; Ovalle, Maria; Matthews, Luke (Journal of Scientific Exploration, 2023)
Episodes of demonic or spirit possession, where individuals perceive their bodies and minds as being controlled by supernatural entities, have been the subject of extensive research across various disciplines. Despite this, the extent to which existing scientific explanations can account for these phenomena is still uncertain, especially in terms of the aspects that remain unexplained. This official review aims to clarify the current scientific understanding of the origins, mechanisms, and causes of these seemingly extraordinary experiences. Our analysis includes 52 documented cases of possession, reviewed from literature published between 1890 and 2023 and incorporating insights from psychology, medicine, anthropology, and theology. We examine common symptom patterns, delve into the research conducted, and evaluate how many cases are still unexplained within the existing behavioral science framework. Quantitative models indicate a 0.01923 probability of a possession case being scientifically unexplained. The likelihood of discovering new, truly unexplained cases of demonic possession in the future is estimated at 0.0031, with a 0.0023 probability of encountering five such cases in a single year. Moreover, we assess the medical and psychological interventions employed in these cases and propose practical guidelines for the safe use of exorcisms and specific pharmacological treatments. This study advocates for the integration of therapeutic interventions, combined with the expertise of anthropologists for culturally sensitive actions and Catholic Church priests for spiritual guidance, including exorcisms where appropriate as determined by ecclesiastical authorities. Our conclusion suggests that integrative approaches provide the most comprehensive clinical support in such cases and underscore how possession episodes challenge our scientific understanding of consciousness and its boundaries.